PENGARUH KUALITAS PELAYANAN DAN STANDAR OPERASIONAL PROSEDUR TERHADAP KEPUASAN PELANGGAN PADA PT POS INDONESIA DI KOTA BATAM - Amin, Al; Realize, Realize (LPPM Universitas Putera Batam, 2019)
Changes and developments in the company have a considerable impact on various fields that follow the world economy, from the industrial economy to the service economy. This research method is quantitative. The sampling technique used in this study is convenient / judgment sampling. The sample used was 105 respondents. The results of the research service quality variables have a positive and significant effect on consumer satisfaction, with a value of 1.991> 1.65978 (t-table) and a significant value of 0.049 <0.05. For standard operational variables the procedure has a positive and significant influence on customer satisfaction with a value of 8.976> 1.65978 (t-table) and a significant value of 0.000 <0.05. While simultaneously service quality and standard operating procedures have a significant effect on customer satisfaction with F count 41.47> 1.39 (f-table), the significance value obtained is 0.000 <α 0, 05. Based on the results of the R Square value (R2) of 0.448 or 44.8%. This means that the variable customer satisfaction can be explained by service quality variables and operational standard procedures 44.8% while the remaining 55.2% is influenced by other factors not included in this study.